2019
DOI: 10.1111/ppa.12982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of virulence and pathogenicity of Alternaria patula on French marigold (Tagetes patula)

Abstract: Alternaria patula, the cause of French marigold leaf black spot and flower blight, was first isolated from seeds of French marigold cv. Queen Sophia. It is described as a new species of Alternaria and has a considerable morphological variation with a preferential pathogenicity to Asteraceae, Solanaceae and Cucurbitaceae plants. Alternaria patula produces an array of pectin depolymerases that can break 1,4-a-glycosidic bonds either by hydrolysis of polygalacturonases (PG, E.C. 3.2.1.15) or via trans-elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However, spore infection and germination can occur within a wide temperature range of between 4 and 35 °C (Chain 2011 ). During infection, Alternaria species produce host-specific, and non-host-specific phytotoxins and extracellular enzymes to destroy plant cell walls at the infection site, which plays a major role in pathogenicity against plants (Wu and Wu 2019 ). Due to their tolerance to wide environmental conditions, Alternaria can infect a range of produce in various geographic locations, which cause the propagation of its mycotoxins (Louro et al 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, spore infection and germination can occur within a wide temperature range of between 4 and 35 °C (Chain 2011 ). During infection, Alternaria species produce host-specific, and non-host-specific phytotoxins and extracellular enzymes to destroy plant cell walls at the infection site, which plays a major role in pathogenicity against plants (Wu and Wu 2019 ). Due to their tolerance to wide environmental conditions, Alternaria can infect a range of produce in various geographic locations, which cause the propagation of its mycotoxins (Louro et al 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore assumed that Alternaria can grow and reproduce around the world, although there is no direct report of this (Blagojević et al., 2020; Yin et al., 2021). In addition, some studies have shown that Alternaria can produce a variety of toxins, which can be divided into host‐selective toxins (HST) and non‐host‐selective toxins (nHST) (Wu & Wu, 2019). Among them, HSTs play a role in plant pathogenicity, while nHSTs can also play important roles in relation to host ranges (causing symptoms on multiple other plant species) and may not be essential for pathogenicity, but may contribute to virulence, posing a threat to the edible safety of berries (Meena & Samal, 2019; Wang, Guo, Luo, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Alternaria is widely distributed and commonly occurs as saprophytes, endophytes and pathogens ( Nishikawa & Nakashima, 2020 ). More than 95% of Alternaria species have a wide range of plant pathogens that can cause a variety of diseases in many economically important crops or ornamental plants, e.g ., early blight in potato and tomato ( Kokaeva et al, 2017 ), black spot and leaf spot in wheat ( Vergnes et al, 2006 ), and leaf spot in cruciferous ( Al-Lami, You & Barbetti, 2018 ), Solanaceae ( Liu et al, 2019 ) and Asteraceae ( Wu & Wu, 2018 ). Therefore, caution should be taken regarding the possible ecological risk in disease transmission on local plants driven by A. adenophora invasion.…”
Section: Introductionmentioning
confidence: 99%